Influence of institutional and structural changes on the financial and economic development of Ukraine - Zhytar , Maksym (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2024)
The article reveals the relevance and necessity of deep reforms in Ukraine to achieve economic revival and integration with European economic systems. The author analyzes significant institutional and structural reforms aimed at improving the economic environment, attracting investment, developing the private sector, and fighting corruption. These reforms cover important areas, including the banking system, public administration, the judiciary, antitrust regulation, and land relations, creating favorable conditions for financial and economic development and the economy’s resilience to external shocks. The article emphasizes that the listed changes have both positive and negative aspects. On the one hand, the reforms contributed to increasing the transparency of management, improving the investment climate, and reducing corruption. On the other hand, the implementation process of some reforms proved to be difficult due to the lack of effective implementation and control mechanisms, as well as external challenges such as military conflict and global economic crises. The author also considers investment risk as an important indicator of institutional and structural changes in the country, pointing to systematic risk caused by country-wide institutional, political, and macro-financial factors, and individual risk determined by specific features of the company’s financial condition. The increase in systematic risk due to hostilities has worsened financing conditions for all businesses, but the distribution of individual risk depends on many factors.